Journal Notes - various authors (GDR Bulletin, 1983)
Reviews of: Sinn und Form Vol. 34, No. 5-6; Vol. 35, No. 1 (Wolfgang Ertl) Neue Deutsche Literatur Vol. 30, No. 7-12 (Peter Beicken) Deutschland Archiv No. 5-8 (Karen Remmler) Die Horen No. 126 and 128 (Geoffrey Davis) Merkur Vol. 36, No. 10 (Geoffrey Davis)